Use of the KineSpring system in the treatment of medial knee osteoarthritis: preliminary results - Madonna, Vincenzo; Condello, Vincenzo; Piovan, Gianluca; Screpis, Daniele; Zorzi, Claudio (Joints, 2015)
Purpose: the purpose of this study was to analyze our preliminary results obtained with the KineSpring system in patients suffering from medial compartment knee osteoarthritis (OA).Methods: between September 2012 and May 2014, 53 patients underwent treatment with the KineSpring system. Patient self-assessment was performed preoperatively and at 3, 6 and 12 months postoperatively, and included the KOOS, Tegner activity score, Lysholm functional knee score, VAS knee pain score, and IKDC score. Device- and procedure-related adverse events were recorded.Results: mean KOOS subscales, except for the Sport/Recreation subscale at six months, improved over time. Mean WOMAC Pain and Function domains, Lysholm score, IKDC score and VAS knee pain score improved over the follow-up period and were significantly improved at 3, 6 and 12 months postoperatively compared to baseline. Mean Tegner score improved slightly over time. In 5 of the 53 (9.4%) patients re-operation was necessary. In 3 patients the device was removed due to infection (one case) or persistent knee pain (two cases). Surgical arthrolysis was performed in two patients.Conclusions: in our preliminary experience, the KineSpring system gave good short-term clinical results.Level of evidence: Level IV, therapeutic case series.
Keywords: KineSpring; medial compartment; knee osteoarthritis; varus; unloading